Screening of ectoparasites from domesticated dogs for bacterial pathogens in Vientiane, Lao PDR - Nguyen, HM; Theppannga, W; Vongphayloth, K; Douangngeun, B; Blacksell, S; Robinson, M (Wiley, 2020)
Arthropod‐borne diseases are widespread worldwide and are a complex interaction between animals, humans and ectoparasites. The understanding of the diversity and epidemiology of organisms transmitted by arthropod vectors, and the role of hosts and vectors in transmission of infections remain limited in Lao PDR. What knowledge does exist is primarily focused on more rural regions of the country. This study screened ectoparasites from domestic dogs in Vientiane city for the presence of bacterial pathogens of zoonotic importance. A total of 3,511 arthropod vectors were collected from 112 dogs. Vectors collected were Rhipicephalus sanguineus ticks, Ctenocephalides felis felis and Ctenocephalides felis orientis fleas and Heterodoxus spiniger lice. A sub‐sample of vectors from each dog was analysed by PCR to identify the potential bacteria. From 129 vector pools, Rickettsia spp. was detected in 6.7% (7/105) pools of ticks, 86.4% (19/22) pools of fleas and both pools of lice. Sequencing analysis confirmed Rickettsia felis in 13 flea pools and one louse pool and Rickettsia asembonensis in six flea pools. Anaplasmataceae was identified in 14.3% (15/105) tick pools and 100% (22/22) flea pools. Sequencing revealed the presence of Anaplasma platys in ticks and Wolbachia pipientis in fleas. Leptospira spp. was detected in one tick and one louse pool, and Brucella spp. was detected in 12.4% (13/105) tick pools. All samples were negative for Bartonella spp., Coxiella burnetii and Borrelia burgdorferi . This is the first study providing evidence of R. asembonensis in fleas in Laos. Results from this study show arthropods are potential vectors to transmit zoonotic infection in Vientiane city, suggesting humans are at risk of zoonotic infections in the city.